Gender Analysis of Aquaculture Value Chain in Northeast Vietnam and Nigeria - Veliu, Atdhe; Gessese, Nebiyeluel; Ragasa, Catherine; Okali, Christine (World Bank, Washington, DC, 2017)
The report is an initiative of the Agriculture and Rural Development Department (ARD) of the World Bank. Aquaculture is the fastest-growing food sector in the world and is expected to contribute more than 50 percent of total fish consumption by 2020. Just over 90 percent of aquaculture production originates in Asia, and nearly 70 percent in China alone. Efforts to expand aquaculture production to meet the ever increasing worldwide demand for seafood continue. Although the boom in international demand for shrimp has drawn attention to this sector, the development potential of aquaculture stems partly from the variety of products, production systems, and scales of production it covers. In comparison with the dominance of large-scale coastal aquaculture systems in Latin America, North America, and Europe, the vast majority of aquaculture production in Asia is carried out in rural areas, is integrated into existing farming systems, takes places on a small scale, depends on the cooperation of family members, and involves large numbers of the rural population. Aquaculture is a promising business venture in many contexts, and the private sector drives and plays a major role in this. The aim of this study is to guide two potential World Bank operations in Vietnam and Nigeria with the aquaculture value chain as their focus. This paper describes the specific contexts of Vietnam and Nigeria and recommends concrete project entry points and actions for gender integration, applying the lessons learned from past experiences.